Leukocyte‐Repelling Biomimetic Immunomagnetic Nanoplatform for High‐Performance Circulating Tumor Cells Isolation. Issue 17 (1st April 2019) - Zhou, Xiaoxi; Luo, Bin; Kang, Ke; Zhang, Yujia; Jiang, Peipei; Lan, Fang; Yi, Qiangying; Wu, Yao
Abstract: Downstream studies of circulating tumor cells (CTCs), which may provide indicative evaluation information for therapeutic efficacy, cancer metastases, and cancer prognosis, are seriously hindered by the poor purity of enriched CTCs as large amounts of interfering leukocytes still nonspecifically bind to the isolation platform. In this work, biomimetic immunomagnetic nanoparticles (BIMNs) with the following features are designed: i) the leukocyte membrane camouflage, which could greatly reduce homologous leukocyte interaction and actualize high‐purity CTCs isolation, is easily extracted by graphene nanosheets; ii) facile antibody conjugation can be achieved through the "insertion" of biotinylated lipid molecules into leukocyte‐membrane‐coated nanoparticles and streptavidin conjunction; iii) layer‐by‐layer assembly techniques could integrate high‐magnetization Fe3 O4 nanoparticles and graphene nanosheets efficiently. Consequently, the resulting BIMNs achieve a capture efficiency above 85.0% and CTCs purity higher than 94.4% from 1 mL blood with 20–200 CTCs after 2 min incubation. Besides, 98.0% of the isolated CTCs remain viable and can be directly cultured in vitro. Moreover, application of the BIMNs to cancer patients' peripheral blood shows good reproducibility (mean relative standard deviation 8.7 ± 5.6%). All results above suggest that the novel biomimetic nanoplatform may serve as a promising tool for CTCs enrichment and detection from clinical samples. Abstract : A creative one‐step homologous cellular membrane extraction and introduction method based on graphene nanosheets is prompted. A facile membrane functionalization route based on lipid anchors is also employed to construct a leukocyte membrane camouflaged immunomagnetic nanoplatform. The as‐gained platform achieves high specificity, enhances antileukocyte absorption ability and shows good sensitivity in blood samples with rare circulating tumor cells.